2021
DOI: 10.3390/ijerph182312841
|View full text |Cite
|
Sign up to set email alerts
|

Region-Specific Associations between Environmental Factors and Escherichia coli in Freshwater Beaches in Toronto and Niagara Region, Canada

Abstract: Poor freshwater beach quality, measured by Escherichia coli (E. coli) levels, poses a risk of recreational water illness. This study linked environmental data to E. coli geometric means collected at 18 beaches in Toronto (2008–2019) and the Niagara Region (2011–2019) to examine the environmental predictors of E. coli. We developed region-specific models using mixed effects models to examine E. coli as a continuous variable and recommended thresholds of E. coli concentration (100 CFU/100 mL and 200 CFU/100 mL).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
3
7
0
Order By: Relevance
“…Our mixed-methods analysis showed a positive average effect of the log geometric mean of E. coli in the previous sample day on geometric mean E. coli concentration, consistent with previous studies elsewhere [ 38 40 ]. Even though beach water sampling was not conducted daily in Vancouver, the positive effect of the previous sample day log E. coli values on the E. coli concentration could indicate the persistence of contamination levels in marine water bodies over several days, conditional on other environmental factors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our mixed-methods analysis showed a positive average effect of the log geometric mean of E. coli in the previous sample day on geometric mean E. coli concentration, consistent with previous studies elsewhere [ 38 40 ]. Even though beach water sampling was not conducted daily in Vancouver, the positive effect of the previous sample day log E. coli values on the E. coli concentration could indicate the persistence of contamination levels in marine water bodies over several days, conditional on other environmental factors.…”
Section: Discussionsupporting
confidence: 91%
“…Still, it is not always the case that such relationships are that different by beach, though they were in this study. For example, in a similar study in Toronto and Niagara, the Niagara beaches were very similar probably due to proximity and most had really excellent water quality, so it might be related to both of those factors and common/different pollution sources [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It received the Blue Flag designation in 2022 as well as prior years, an international certification program that assesses water quality and other environmental and safety criteria [28]. However, elevated E. coli levels occasionally occur throughout the summer season leading to swimming advisories [28,29], suggesting one or more recurring sources of fecal contamination.…”
Section: Study Design and Settingmentioning
confidence: 99%
“…Multiple pollution sources and various environmental factors play a role in the fecal contamination of recreational waters [12]. Numerous studies have found that fecal contamination of fresh lake water is associated with recent rainfall [13][14][15]. The growth and survival of FIB in freshwater can also be determined by air and water temperature [14,16].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have found that fecal contamination of fresh lake water is associated with recent rainfall [13][14][15]. The growth and survival of FIB in freshwater can also be determined by air and water temperature [14,16]. The FIB concentration in fresh lake water also tends to decrease with increased ultraviolet (UV) solar radiation [14].…”
Section: Introductionmentioning
confidence: 99%